The Network of Conceptual Metaphors of GOD and JESUS in the Fourth Gospel - Vaivadaitė-Kaidi, Eglė (Respectus Philologicus, 2018)
[only abstract in English; full article and abstract in Lithuanian]This article analyses the metaphoric language pertaining to the concepts of GOD and JESUS in the modern translation of the Fourth Gospel into the Lithuanian language (Kavaliauskas 2009). The aim of the research is to reveal the system of conceptual metaphors defining these concepts in the text. The investigation was conducted following MIP(VU) as a method of identifying metaphoric language in discourse following the framework of the Conceptual Metaphor Theory.The study reveals that the concepts of GOD and JESUS are defined by a complex system of closely related conceptual metaphors related to each other through various conceptual mappings. The system is based on the oppositions of UP and DOWN, LIGHT and DARK, GOOD and BAD, and is constituted of the source domains of FAMILY, POWER RELATIONSHIPS, LAW, AGRICULTURE, and PHYSICAL REALITY. The most common conceptual metaphors are the GOD – FATHER and JESUS – SON metaphors. They are the basis of other cases of personification of GOD and JESUS identified, namely: KING, SHEPHERD, JUDGE, SENDER, SOWER, WINE-MAKER, etc. All these conceptual metaphors may be related through the conceptual mappings of AUTHORITY and POWER. The authority and power of the Father are passed to the Son, who comes to this world to continue the works of his Father and inherits his Father’s place in the hierarchy of the family.
Keywords: Conceptual Metaphor, Source Domain, Target Domain, the Fourth Gospel, Bible Translations